DETERMINAN TAX AVOIDANCE PADA EMITEN TERBAIK VERSI FORBES INDONESIA 2019 - dewi murdiawati (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The results of previous studies still indicate inconsistencies related to the determinants of tax avoidance. The aims of this research is to examine the effect of good corporate governance (GCG), financial factors and non-financial factors on the tax avoidance in companies listed in the Forbes Indonesia 2019 as the The best Companies. The sampling technique that used in this research was purposive sampling from 50 best companies version Forbes Indonesia 2019, and duration data of companies from 2016-201. Total the number of sample was 130 companies. The data were analyzed by using Partial Least Square (PLS) method. The results show that good corporate governance (GCG), financial factors and non-financial factors influence the tax avoidance.